2011
DOI: 10.1002/hep.24314
|View full text |Cite
|
Sign up to set email alerts
|

Diclofenac inhibits tumor necrosis factor‐α‐induced nuclear factor‐κB activation causing synergistic hepatocyte apoptosis

Abstract: Drug-induced liver injury (DILI) is an important clinical problem. It involves crosstalk between drug toxicity and the immune system, but the exact mechanism at the cellular hepatocyte level is not well understood. Here we studied the mechanism of crosstalk in hepatocyte apoptosis caused by diclofenac and the proinflammatory cytokine tumor necrosis factor a (TNF-a). HepG2 cells were treated with diclofenac followed by TNF-a challenge and subsequent evaluation of necrosis and apoptosis. Diclofenac caused a mild… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

13
72
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 89 publications
(86 citation statements)
references
References 37 publications
13
72
0
Order By: Relevance
“…Cytokine-mediated proapoptotic signaling is an important component in the pathophysiology of drug-induced liver injury (43,44). It has been reported that TNFa severely enhances liver damage caused by various xenobiotics (43,(45)(46)(47) and is the major cytokine to be excreted by the liver stationary macrophages (Kupffer cells) in response to hepatocyte damage (33). It is possible that T-DM1-mediated secretion of TNFa, which activates proapoptotic signaling pathway, significantly enhances the liver damage that is initially caused by DM1-mediated intracellular stress.…”
Section: Control Trastuzumab T-dm1 T-dm1mentioning
confidence: 99%
“…Cytokine-mediated proapoptotic signaling is an important component in the pathophysiology of drug-induced liver injury (43,44). It has been reported that TNFa severely enhances liver damage caused by various xenobiotics (43,(45)(46)(47) and is the major cytokine to be excreted by the liver stationary macrophages (Kupffer cells) in response to hepatocyte damage (33). It is possible that T-DM1-mediated secretion of TNFa, which activates proapoptotic signaling pathway, significantly enhances the liver damage that is initially caused by DM1-mediated intracellular stress.…”
Section: Control Trastuzumab T-dm1 T-dm1mentioning
confidence: 99%
“…Specifically, cells were seeded in normal growth medium at 60,000 cells/ml, with 2.0 ml/well in 6-well culture plates, and grown for 2 days. On day 3, the cells were washed with serum-free DMEM and then incubated in serumfree DMEM for an additional 24 h. Subsequently, the cells were washed and then incubated with DMEM containing 10 ng/ml TNF-α [21], 25 ng/ml IL-6 [22], or both of these compounds for 0, 4, 8 or 24 h. All of the cell experiments were performed in triplicate.…”
Section: Proinflammatory Factor Assaymentioning
confidence: 99%
“…HepG2 cells were cultured for 24 h in complete medium containing FFAs and then cultured for an additional 24 h with the proinflammatory factors TNF-α (10 ng/ml) [21] and IL-6 (25 ng/ml) [22]. The cells were collected after 0, 4, 8, and 24 h to determine the expression levels of the six selected miRNAs.…”
Section: The Effect Of Proinflammatory Factors On Mirna Expressionmentioning
confidence: 99%
“…NF-B regulates the transcription of a wide variety of target genes, including inflammation-related genes (e.g., those encoding cytokines and chemokines, Cox-2, and those encoding tumor necrosis factor alpha [TNF-␣]) (10). NF-B is activated by a variety of inflammatory stimuli, such as interleukin 1 (IL-1) and TNF-␣, and inhibited by IL-10 and nonsteroidal anti-inflammatory drugs (9,11,12). Moreover, aberrant NF-B activity is frequently involved in diseases, and the function of RelA is altered in many cancers (13).…”
mentioning
confidence: 99%